2019
DOI: 10.1080/00207543.2019.1570376
|View full text |Cite
|
Sign up to set email alerts
|

Information systems for supply chain management: a systematic literature analysis

Abstract: Information systems (IS) impact supply chain management (SCM) on processes such as planning, sourcing, and delivering, and at levels ranging from tactical operations to organisational strategy. The vast scope of IS and SCM relationships have resulted in diverse and disintegrated research on the topic. This paper offers a systematic literature analysis at the intersection of supply chain and information systems (SCIS), aiming to provide a classification for existing areas of research. This research is based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 88 publications
(94 reference statements)
1
24
0
5
Order By: Relevance
“…IoT-based infrastructure (C4) is the third important cause group and clustered in the independent variable. IoT-based infrastructure systems provide important data of government and organisational data for decision-making by the FF about global demand fluctuation, regulating quality standards, monitoring for adjusting logistics action before any accidents (Daneshvar Kakhki and Gargeya 2019 ). Cold chain for perishable products (C13) is the fourth important cause group and categorised under linkage variable.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…IoT-based infrastructure (C4) is the third important cause group and clustered in the independent variable. IoT-based infrastructure systems provide important data of government and organisational data for decision-making by the FF about global demand fluctuation, regulating quality standards, monitoring for adjusting logistics action before any accidents (Daneshvar Kakhki and Gargeya 2019 ). Cold chain for perishable products (C13) is the fourth important cause group and categorised under linkage variable.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Information sharing is an important topic in production and operations research (Chandra, Grabis, and Tumanyan 2007;Daneshvar Kakhki and Gargeya 2019;Lei et al 2019;Shen, Choi, and Minner 2019). Numerous studies have investigated the impacts of information sharing on various SC entities and provided important insights on how to leverage the benefits of information sharing to improve the production and operations systems (Chan and Chan 2009;Chiang and Feng 2007;Davis et al 2011;Huang, Li, and Ho 2016;Wu et al 2011).…”
Section: Production Research Literature On Information Sharing Sc Lementioning
confidence: 99%
“…IS can be a way of achieving sustainable competitive advantages by utilizing unique enterprise attributes [10]. Previous literature found that enterprises can improve firm performance by reducing costs and delivery time, and enhancing customer service and reliability with help of ICT implementation [11]. Consequently, the potential of IS to enhance management decision-making capabilities and productivity by adopting enterprise resource systems, supply chain collaboration support systems [12], and social reference systems to support sustainable social commerce sales, have been explored [13].…”
Section: Introductionmentioning
confidence: 99%